Immunotherapy Goes Local: The Central Role of Lymph Nodes in Driving Tumor Infiltration and Efficacy - van Pul, Kim M.; Fransen, Marieke F.; van de Ven, Rieneke; de Gruijl, Tanja D. (Frontiers in Immunology, 2021)
Immune checkpoint blockade (ICB) has changed the therapeutic landscape of oncology but its impact is limited by primary or secondary resistance. ICB resistance has been related to a lack of T cells infiltrating into the tumor. Strategies to overcome this hurdle have so far focused on the tumor microenvironment, but have mostly overlooked the role of tumor-draining lymph nodes (TDLN). Whereas for CTLA-4 blockade TDLN have long since been implicated due to its perceived mechanism-of-action involving T cell priming, only recently has evidence been emerging showing TDLN to be vital for the efficacy of PD-1 blockade as well. TDLN are targeted by developing tumors to create an immune suppressed pre-metastatic niche which can lead to priming of dysfunctional antitumor T cells. In this review, we will discuss the evidence that therapeutic targeting of TDLN may ensure sufficient antitumor T cell activation and subsequent tumor infiltration to facilitate effective ICB. Indeed, waves of tumor-specific, proliferating stem cell-like, or progenitor exhausted T cells, either newly primed or reinvigorated in TDLN, are vital for PD-1 blockade efficacy. Both tumor-derived migratory dendritic cell (DC) subsets and DC subsets residing in TDLN, and an interplay between them, have been implicated in the induction of these T cells, their imprinting for homing and subsequent tumor control. We propose that therapeutic approaches, involving local delivery of immune modulatory agents for optimal access to TDLN, aimed at overcoming hampered DC activation, will enable ICB by promoting T cell recruitment to the tumor, both in early and in advanced stages of cancer.